STUDY OF SCIENCE LITERACY ABILITY OF CHEMISTRY PRE-SERVICE TEACHERS IN HYDROPONICS PRACTICUM - Bahriah, Evi Sapinatul; Siti Suryaningsih; Ivan Muhammad Maful (JCER (Journal of Chemistry Education Research), 2024)
The ability of scientific literacy of indonesian student categorized as low. One of the factor that contribute is that the ability of a scientific literacy of a teacher. The hydroponics practical in a biotechnology’s subject, can be measure the ability of scientific literacy of a student because there is a science process in it. The aim of this reasearch is to determine the ability of scientific literacy of chemisty pre-service Teachers for the knowledge and competency’s aspects in a hydroponics topic. The method that used in this reasearch was quantitative descriptive analysis and the technique of data collection by spreading the instrument in a purposive sampling technique to 50 chemisty pre-service teachers. The instrment that used was 10 items of essay questions. The data was analyse with a scoring method and then will change it into a percentage. Based on the reasearch, the ability of scientific literacy of a student for knowledge’s aspect is 68.5% and for the competency is 62.2%. From that data, it can conclude that the ability of scientific literacy of chemistry chemisty pre-service teachers for knowledge and comptency aspects categorized good.